Recent advances in date palm genomics: A comprehensive review - Rahman, Hifzur; Vikram, Prashant; Hammami, Zied; Singh, Rakesh Kumar (Frontiers in Genetics, 2022)
As one of the oldest fruit trees of the Arabian peninsula, other Middle-Eastern countries, and also North Africa, the date palm (Phoenix dactylifera L.), is highly significant for the economy of the region. Listed as part of UNESCO’s Intangible Cultural Heritage of Humanity, the date palm is believed to be the first tree cultivated by human beings, and was probably first harvested for its fruit nearly 7,000 years ago. Initial research efforts in date palm genetics focused on understanding the genetic diversity of date palm germplasm collections and its phylogenetic history, both important prerequisites for plant improvement. Despite various efforts, the center of origin of the date palm is still unclear, although genomic studies suggest two probable domestication events: one in the Middle East and the other in North Africa, with two separate gene pools. The current review covers studies related to omics analyses that have sought to decipher the present genetic diversity of the date palm. With advances and cost reductions in sequencing technologies, rapid progress has been made in the past few years in date palm genomics research. Along with organellar genomes, several reference genomes of the date palm are now available. In addition, several genotypes have been re-sequenced, either to detect single nucleotide polymorphisms (SNPs), or to study domestication and identification of key genes/loci associated with important agronomic traits, such as sex, fruit color, and sugar composition. These genomics research progress has paved the way to perform fast-track and precise germplasm improvement processes in date palm. In this study, we review the advances made in the genetics and genomics of the date palm so as to strategize targeted crop improvement plans for marginal areas of the Middle Eastern peninsula, North Africa, and other parts of the world.